Business Analysis and BEP of Household-Scale Coconut Processing in the Igo Jaya Women Farmer Group in Jaya Village, Tidore City Islands (Agrikan Jurnal Agribisnis Perikanan, 2022)
This research was conducted for three months starting from July to October 2022 in the Igo Jaya farmer group in the Jaya sub-district, Tidore Kepulauan city, which consisted of ten members and all of them were used as samples. The aim of the study was to analyze how much the costs, receipts and income were derived from the coconut processing business in the Igo Jara women farmer group in the city of Tidore Islands and to analyze the BEP in the form of BEP units and sales BEP. Based on the results of the calculation of costs, receipts, and income for the ten products produced, it shows that all of them benefit with the largest profit gain, namely VCO and coconut oil products because the selling price of the two products is quite high, namely IDR 42,997 per 250 ml bottle for the product. VCO and IDR 42,411 per 500 ml bottle for coconut oil products. Based on the calculation results for unit BEP and sales BEP for the ten products, it shows that the highest unit BEP value is found in coconut juice products and the highest sales BEP value is found in coconut oil products. For BEP units, it means that the breakeven point can be obtained in the coconut juice business if it is able to sell 53 units. As for BEP sales, it means that the breakeven point can be obtained in the coconut oil business if you are able to make sales of IDR 1,034,642.
Keywords: Analisis Usaha; Break Even Point; Pengolahan Kelapa; Usaha Skala Rumah Tangga; Kelompok Wanita Tani